What are Lumineers and How Do They Differ from Veneers What is Single-Stage Implantation? (International Journal of Scientific Trends, 2025)
Lumineers are thin plates with the thickness of contact lenses that are fixed to the teeth without turning. In fact, these are the same veneers, only more effective, improved and safer. They look more natural, which is why they are called “hollywood veneers.” Their creators were tasked with creating a hollywood smile for many years without harming their teeth.